Micron-sized graphite microsphere-based composite phase change material and preparation method thereof

Micron-scale graphite microspheres were prepared by electronic atomizer and composite phase change materials were prepared by impregnation and thermal filtration methods, which solved the problem of low loading rate of microspheres in the prior art and achieved the improvement of high loading rate and thermal conductivity.

CN119432328AActive Publication Date: 2025-02-14CHINA UNIV OF GEOSCIENCES (WUHAN) +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411317714.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-02-14
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

In the prior art, microspheres prepared by spray drying cannot form porous aerogel microspheres, resulting in a low loading rate of composite phase change materials and difficult to improve performance.

Method used

Micron-scale graphite microspheres were prepared by spraying the nanographite cellulose mixed solution into liquid nitrogen using an electronic atomizer, and micron-scale graphite microsphere matrix composite phase change material was prepared by impregnation and thermal filtration.

Benefits of technology

By forming a micro aerogel porous structure, the loading rate and thermal conductivity of the composite phase change material are significantly improved, and the phase change enthalpy value remains high after multiple cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432328A_ABST
    Figure CN119432328A_ABST
Patent Text Reader

Abstract

The invention discloses a micron-sized graphite microsphere-based composite phase change material and a preparation method thereof. The invention relates to the technical field of phase change materials. The preparation method comprises the following steps: S1, dispersing nano-graphite and nano-cellulose in deionized water, and then carrying out ball milling to obtain a nano-graphite cellulose mixed solution; s2, spraying the nano-graphite cellulose mixed solution into a container filled with liquid nitrogen by using an electronic atomizer, then sieving microspheres in the container, and freeze-drying the microspheres to obtain micron-sized graphite microspheres; and S3, dipping the micron-sized graphite microspheres in the molten phase change material for a period of time, and then carrying out hot filtration to obtain the micron-sized graphite microsphere-based composite phase change material. According to the invention, nano graphite and nano cellulose are mixed and subjected to ball milling and then sprayed out by using an electronic atomizer to prepare microspheres, due to the formation of a micro aerogel porous structure, the microspheres can better absorb a phase change material, the heat storage capability and the heat-conducting property are greatly improved, and the microspheres still have a relatively high phase change enthalpy value after multiple cycles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of phase change materials, and in particular to a micron-grade graphite microsphere-based composite phase change material and a preparation method thereof. Background Art

[0002] Latent heat storage technology using phase change materials as heat storage functional bodies is widely used in the fields of solar energy storage, industrial waste heat recovery and building energy conservation. Leakage is the main problem that hinders the application of phase change materials. Encapsulating and preparing shaped composite phase change materials using porous materials as the matrix is ​​an important method to solve this problem.

[0003] The material and size of the porous material itself also greatly affect the performance of the composite phase change material. In the prior art, microsphere matrix encapsulation is often used to prepare shaped composite phase change materials. The general methods for producing microspheres include emulsification solvent volatilization method, phase separation method, spray drying method and membrane emulsification method. The microspheres prepared by spray drying method are generally obtained by spraying the mixed solution into an inert gas or high-temperature gas and drying to obtain a powder structure. Porous aerogel microspheres cannot be formed, resulting in problems such as low loading rate, and it is difficult to improve the original performance. Summary of the invention

[0004] The purpose of the present invention is to provide a micron-sized graphite microsphere-based composite phase change material and a preparation method thereof in view of the above-mentioned deficiencies in the prior art.

[0005] A method for preparing a micron-sized graphite microsphere-based composite phase change material of the present invention comprises the following steps: S1, dispersing nano-graphite and nano-cellulose in deionized water and then ball-milling to obtain a nano-graphite-cellulose mixed solution; S2, using an electronic atomizer to spray the nano-graphite cellulose mixed solution into a container filled with liquid nitrogen, then sieving the microspheres in the container, and freeze-drying the microspheres to obtain micron-sized graphite microspheres; S3, immersing the micron-sized graphite microspheres in the molten phase change material for a period of time and then filtering the mixture with heat to obtain the micron-sized graphite microsphere-based composite phase change material.

[0006] Furthermore, the mass ratio of nano-graphite to nano-cellulose is 1-10:1.

[0007] Furthermore, the mass volume ratio of nanographite to deionized water is 1-10:100 g / ml.

[0008] Furthermore, the ball milling speed is 400-600 r / min and the time is 2-4 h.

[0009] Furthermore, the phase change material is paraffin.

[0010] Furthermore, the specific operation of step S3 is: firstly put the micron-sized graphite microspheres and the phase change material into a container and then evacuate the container in a vacuum drying oven, then react at 80°C for 2h to obtain a micron-sized graphite microsphere-based composite phase change material, and then perform heat filtration in an oven at 80°C.

[0011] Further, freeze drying was performed for 72 hours.

[0012] A micron-sized graphite microsphere-based composite phase change material prepared by the above-mentioned preparation method.

[0013] Furthermore, the loading rate of the phase change material in the micron-sized graphite microsphere-based composite phase change material is 65%-70%.

[0014] The present invention ball-mills and emulsifies the solution of nano-graphite and nano-cellulose to form an emulsion in the mixed solution, so that the sprayed droplets can be cooled in liquid nitrogen to form microspheres; the nozzle of the electronic atomizer is of micron level, ensuring that the sprayed droplets are also of micron level, and the finally obtained microspheres are also of micron level.

[0015] When preparing the composite phase change material, the material is first evacuated to exhaust the air in the microspheres so that the high-temperature molten paraffin liquid can flow smoothly into the pores of the microspheres. The microporous structure of the microspheres can bind PW through capillary force to prevent PW from leaking due to melting phase change.

[0016] In the present invention, the microspheres prepared by mixing nano-graphite and nano-cellulose, ball-milling and then spraying them out with an electronic atomizer can form a micro-aerogel porous structure, which can better absorb the phase change material, thereby improving the loading rate. In addition, because graphite is also used as the raw material of the microspheres, the heat storage capacity and thermal conductivity of the micron-scale graphite microsphere-based composite phase change material are greatly improved, and it still has a high phase change enthalpy value after multiple cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a real photo of the micron-sized graphite microspheres prepared in the present invention.

[0018] Figure 2 This is a real photo of the micron-sized graphite microsphere-based composite phase change material prepared by the present invention.

[0019] Figure 3 It is the DSC chart of Example 1-5.

[0020] Figure 4a -e is the BET diagram of Example 1-5.

[0021] Figure 5are scanning electron microscope images of Examples 1-5; wherein (a)-(b) are electron microscope images of Example 1, (c)-(d) are electron microscope images of Example 2, (e)-(f) are electron microscope images of Example 3, (g)-(h) are electron microscope images of Example 4, and (i)-(j) are electron microscope images of Example 5. DETAILED DESCRIPTION

[0022] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0023] The present invention is implemented by the following technical solution, including the following process steps: (1) Preparation of mixed solution of micron-sized graphite microsphere precursor Add 30 g of nanocellulose aqueous solution with a solid content of 2% into a 100 ml beaker, then measure 30 mL of deionized water and add it to the beaker for mixing, add 0.6 g, 1.8 g, 3 g, 4.2 g and 5.4 g of nanographite respectively into the mixed solution, stir with a magnetic stirrer for 30 min, place the solution in a planetary ball mill for 3 h, the speed of the ball mill is 500 r / min, pour the obtained mixed solution into a 100 ml beaker to obtain a nanographite cellulose mixed solution.

[0024] (2) Preparation of micron-sized graphite microspheres The obtained 60 ml nano-graphite cellulose mixed solution was added to the purchased electronic atomizer for preparation, and then 2 L of liquid nitrogen was poured into the Dewar flask for standby use. The nano-graphite cellulose mixed solution was sprayed into the Dewar flask filled with liquid nitrogen using the electronic atomizer. The electronic atomizer was stopped after each 10 ml was sprayed, and the spraying operation was performed again after waiting for five minutes. After all the solutions were sprayed, the excess liquid nitrogen in the Dewar flask was poured back into the liquid nitrogen storage bottle after waiting for another five minutes. A sieve was placed between the Dewar flask and the liquid nitrogen storage bottle, and the prepared microspheres were poured onto the sieve, and then transferred to a beaker. After sealing with filter paper, the microspheres were dried in a freeze dryer for 72 hours to obtain micron-sized graphite microspheres, such as Figure 1 shown.

[0025] (3) Preparation of microsphere-based composite phase change materials Weigh 1g of micron-sized graphite microsphere powder and 3g of paraffin wax in a beaker; put the beaker into a vacuum drying oven, evacuate the vacuum, and react at 80°C for 2h to obtain a micron-sized graphite microsphere-based paraffin wax composite phase change material, and then perform heat filtration in an oven at 80°C to finally obtain a micron-sized graphite microsphere-based composite phase change material, such as Figure 2 shown.

[0026] Example 1 Weigh 0.6g of nano-graphite powder, 30g of 2wt.% cellulose solution and 30ml of deionized water into a 100ml beaker, stir the solution in the beaker on a magnetic stirrer for half an hour, put the mixed solution in the beaker into a ball mill and grind for 3h, then take out the mixed solution from the ball mill, use an electronic atomizer to spray 60ml of the solution six times, 10ml each time, into the liquid nitrogen of a Dewar flask, with an interval of five minutes each time, put the frozen microspheres into a vacuum freeze dryer and dry for 72 hours before taking out to obtain micron-sized graphite microspheres.

[0027] After compounding micron-sized graphite microspheres and excess paraffin wax and then performing heat filtration, the obtained composite phase change material has a melting enthalpy of 117.3 J / g, a solidification enthalpy of 113.9 J / g, and a thermal conductivity of 0.6235 W / (m·k). According to the BET test, the material has a specific surface area of ​​16.5332 m² / g, a pore volume of 0.318644 cm³ / g, and an average pore diameter of 28.8965 nm.

[0028] Example 2 1.8 g of nanographite powder, 30 g of 2 wt.% cellulose solution and 30 ml of deionized water were weighed, and the rest was the same as in Example 1.

[0029] The melting enthalpy of the obtained composite phase change material is 137.2 J / g, the solidification enthalpy is 132.5 J / g, and the thermal conductivity is 0.6772 W / (m·k). According to the BET test, the specific surface area of ​​the material is 69.2373 m² / g, the pore volume is 0.668389 cm³ / g, and the average pore diameter is 35.3571 nm.

[0030] Example 3 3 g of nano-graphite powder, 30 g of 2 wt.% cellulose solution and 30 ml of deionized water were weighed into a 100 ml beaker. The other conditions were the same as those in Example 1.

[0031] The melting enthalpy of the obtained composite phase change material is 121.7 J / g, the solidification enthalpy is 116.2 J / g, and the thermal conductivity is 0.7325 W / (m·k). According to the BET test, the specific surface area of ​​the material is 62.2777 m² / g, the pore volume is 0.533866 cm³ / g, and the average pore diameter is 31.8875 nm.

[0032] Example 4 4.2 g of nanographite powder, 30 g of 2 wt.% cellulose solution and 30 ml of deionized water were weighed into a 100 ml beaker. The other steps were the same as those in Example 1.

[0033] The melting enthalpy of the obtained composite phase change material is 127.9 J / g, the solidification enthalpy is 124.3 J / g, and the thermal conductivity is 0.8023 W / (m·k). According to the BET test, the specific surface area of ​​the material is 58.9647 m² / g, the pore volume is 0.507495 cm³ / g, and the average pore diameter is 31.9188 nm.

[0034] Example 5 5.4 g of nanographite powder, 30 g of 2 wt.% cellulose solution and 30 ml of deionized water were weighed into a 100 ml beaker. The other steps were the same as those in Example 1.

[0035] The melting enthalpy of the obtained composite phase change material is 102.3 J / g, the solidification enthalpy is 91.2 J / g, and the thermal conductivity is 0.6323 W / (m·k). According to the BET test, the specific surface area of ​​the material is 8.8841 m² / g, the pore volume is 0.149452 cm³ / g, and the average pore diameter is 25.7325 nm.

[0036] Comparative Example 1 Direct use of halloysite composite paraffin: Weigh 3 g of halloysite powder and compound it with paraffin wax, then filter it hot.

[0037] The melting enthalpy of the obtained composite phase change material is 72.2 J / g, the solidification enthalpy is -73.09 J / g, the thermal conductivity is 0.25 W / (m·k), and the loading rate is only 33.6%.

[0038] Comparative Example 2 The nanographite in the raw material is replaced with halloysite to prepare the composite phase change material: 3 g of halloysite powder, 30 g of 2 wt.% cellulose solution and 30 ml of deionized water were weighed into a 100 ml beaker. The other steps were the same as those in Example 1.

[0039] The melting enthalpy of the obtained composite phase change material is -147.6 J / g, the solidification enthalpy is 150.8 J / g, the loading rate is increased from 33.6% to 68%, and the thermal conductivity is 0.3266 W / (m·k).

[0040] Comparative Example 3 Directly use nano graphite to compound paraffin: Weigh 3 g of nanographite and mix it with excess paraffin wax, then perform hot filtration.

[0041] The melting enthalpy of the obtained composite phase change material is -77.53 J / g, the solidification enthalpy is 82.08 J / g, the thermal conductivity is 0.5022 W / (m·k), and the loading rate is only 38%.

[0042] Table 1 Enthalpy value comparison table

[0043] From the data in Table 1 and Figure 3 It can be seen that after the microspheres are prepared, the loading rate and thermal conductivity of the microsphere-based composite phase change material are greatly improved compared with the original composite phase change material. The heat storage performance of Example 2 is also the best among the five embodiments. From Figure 4 and the BET test data, it can be seen that the specific surface area, pore volume and average pore size of Example 2 are the largest among the five embodiments, which can explain the highest adsorption rate of the phase change material in Example 2. From the above data, it can be seen that as the ratio of nanographite to cellulose increases, the thermal performance of the composite phase change material first increases and then decreases.

[0044] For matters not mentioned above, the prior art applies.

[0045] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a micron-sized graphite microsphere-based composite phase change material, characterized in that: The steps include: S1, dispersing nano-graphite and nano-cellulose in deionized water and then ball-milling to obtain a nano-graphite-cellulose mixed solution; S2, using an electronic atomizer to spray the nano-graphite cellulose mixed solution into a container filled with liquid nitrogen, then sieving the microspheres in the container, and freeze-drying the microspheres to obtain micron-sized graphite microspheres; S3, immersing the micron-sized graphite microspheres in the molten phase change material for a period of time and then filtering the mixture with heat to obtain the micron-sized graphite microsphere-based composite phase change material.

2. The preparation method according to claim 1, characterized in that: The mass ratio of nano-graphite to nano-cellulose is 1-10:

1.

3. The preparation method according to claim 1, characterized in that: The mass volume ratio of nanographite to deionized water is 1-10:100 g / ml.

4. The preparation method according to claim 1, characterized in that: The ball milling speed is 400-600 r / min and the time is 2-4h.

5. The preparation method according to claim 1, characterized in that: The phase change material is paraffin.

6. The preparation method according to claim 5, characterized in that: The specific operation of step S3 is: firstly put the micron-sized graphite microspheres and the phase change material into a container and then evacuate the container in a vacuum drying oven, then react at 80°C for 2h to obtain the micron-sized graphite microsphere-based composite phase change material, and then perform heat filtration in an oven at 80°C.

7. The preparation method according to claim 1, characterized in that: Freeze-dry for 72 hours.

8. A micron-sized graphite microsphere-based composite phase change material prepared by the preparation method according to any one of claims 1 to 7.

9. The micron-sized graphite microsphere-based composite phase change material according to claim 8, characterized in that: The loading rate of the phase change material in the micron-sized graphite microsphere-based composite phase change material is 65%-70%.

Citation Information

Patent Citations

  • Microcapsule phase change material and preparation method thereof

    CN106753261A

  • Ternary composite mineral microsphere-based phase change heat storage material as well as preparation method and application thereof

    CN114058337A

  • Three-dimensional porous attapulgite microsphere as well as preparation method and application thereof

    CN115430372A

  • Phase change heat storage material based on microcapsule coating and preparation method thereof

    CN118496818A

  • Chemical-free production of hollow graphene balls

    WO2020023578A1